Pengaruh Variasi Perlakuan Alkali terhadap Kekuatan Tarik Komposit Berpenguat Serat Eceng Gondok - Moch. Daffa Afif R. Tausa; Pranowo Sidi; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Water hyacinth (Eichhornia crassipes) is a weed plant in aquatic areas that lives floating in waters. Water hyacinth has a very fast reproduction so that this plant is considered as a plant that damages the environment. In this research, water hyacinth fiber-reinforced composites were made. The main variables of this study were the volume fraction variation of 15% and the alkaline process using NaOH concentration of 0% and 5% immersion for 2 hours with the tensile testing procedure referring to ASTM D 3039. From the results of the study obtained the average maximum tensile strength 19.71 ± 4.60 MPa at 5% NaOH delignification for 2 hours and the lowest average tensile strength at 0% NaOH delignification for 2 hours 14,76 ± 1,98 MPa.